The elevation training mask induces modest hypoxaemia but does not affect heart rate variability during cycling in healthy adults - Hyun Chul Jung; Nun Hee Lee; Smith D. John; Sukho Lee (Termedia Publishing House, 2018)
This study examined the acute effects of the elevation training mask (ETM) on haemodynamics and heart rate variability (HRV) at rest, during cycling, and during recovery in healthy adults. Fifteen healthy male (N=9) and female (N=6) adults (27.0 ± 1.14 years) completed two trials with the mask (MASK) and without the mask (CON). The 40-minute cycling exercise protocol included 10-minute phases of (1) rest, (2) 50% of VO 2peak cycling, (3) 70% of VO 2peak cycling, and (4) recovery. Blood pressure and pulse oximetry saturation (S P O 2 ) were measured at each phase. An Actiwave-Cardio ECG monitor (CamNtech, UK) was used to measure HRV variables including time and frequency domains. A greater response in systolic blood pressure (p=.035) was observed at rest while S P O 2 (p=.033) was lower during high-intensity cycling (70% of VO 2peak ) in the MASK trial. The HRV indices were not different between trials during cycling. However, heart rate (p=.047) was greater while inter-beat interval and sympathovagal balance (the ratio between low-frequency and high-frequency components; ln LF/HF, p=.01) were lower in the MASK than the CON trials during recovery. Wearing an ETM during high-intensity cycling (70% of VO 2peak ) induces modest hypoxaemia. Although this device did not affect HRV changes during cycling, it seems to delay the cardiac-autonomic recovery from exercise. Healthy adults may be required to perform high-intensity exercise with an ETM to simulate a hypoxic environment, but future studies are needed to determine whether repeated exposure to this condition provides similar benefits as altitude training.